Educação básica conectada: fluência tecnológico-pedagógica e a gestão escolar - Pietrobelli, Sirlei (2023)
Technological-Pedagogical Fluency (FTP) is the learning and knowledge necessary to integrate technologies into the pedagogical process, in a way that constantly reflects on practice and realizes how this action-reflection-action in everyone's education. From this perspective, the general objective of the dissertation is to understand the basic theoretical-practical knowledge of school managers' FTP for the development of pedagogical, administrative and financial activities in Basic Education. Qualitative research evolved as a methodological approach to DesignBased Research (DBR). The delimitation, organization, analysis and synthesis of data occurred from three Cartographic Matrices: the Dialogical-Problematizing Matrix (MDP), the Thematic-Organizing Matrix (MTO) and the Thematic-Analytical Matrix (MTA). The data was produced through document analysis, participant observation and semi-structured interviews with two managers from the state Basic Education network of Palmeira das Missões. And as a product arising from research in DBR, the “Podcast Café Fluente” was produced, based on the managers' conceptions about FTP and its relevance in the three pedagogical, administrative and financial dimensions. Thus, it is concluded that having basic knowledge of FTP enhances the development of management action as a whole. FTP in school management is a recent approach that requires public policies for continued training for managers, in accordance with the demands of everyday school life, taking into account the particularities of the contexts and everyone involved.